Efficacy of the PanCareFollowUp eHealth Lifestyle Intervention for Survivors of Childhood, Adolescent and Young Adult Cancer - van den Oever, Selina R; Bouwman, Eline; van der Pal, Helena J H; Steensma, Philippa C; Araujo-Soares, Vera; Brown, Morven; Kepak, Tomas; Kepakova, Katerina; Fiocco, Marta; Fremouw, Lucy M M; Koopman, Maria M W; van Litsenburg, Raphaële R L; et al. (Cancer medicine, 2025)
PURPOSE: A healthy lifestyle may prevent or mitigate late effects in childhood, adolescent and young adult (CAYA) cancer survivors. To support survivors in adopting healthier behaviours, the PanCareFollowUp (PCFU) Lifestyle intervention was developed, encompassing 4 months of online lifestyle coaching aimed at achieving a personal lifestyle goal. The aims of this study were to (1) determine the efficacy of this intervention on lifestyle outcomes over time and (2) identify predictors for goal achievement. PATIENTS AND METHODS: Fifty-eight survivors were enrolled. Outcomes were assessed at baseline (T0), after 4 months of coaching (T1) and after 4 months of follow-up (T2). The primary outcome included the percentage of survivors successful in achieving and sustaining their goal, whereas secondary outcomes included differences in body mass index (BMI), diet and physical activity. To evaluate the adjusted, longitudinal effects on secondary outcomes, linear mixed models were estimated. Predictors for goal achievement were identified through logistic regression analysis. RESULTS: At T1 and T2, 68% and 76% of goals were achieved or sustained, respectively. Mean differences between T2 and T0 showed significant improvements in BMI (-0.5 kg/m2), diet (-0.6 points) and physical activity (+7.7 h/week). Estimation of multivariable models also showed positive effects. Participants with a lower BMI and fewer depressive feelings at baseline were more likely to achieve and/or sustain their goals at T2. CONCLUSION: Findings suggest that the PCFU Lifestyle intervention supports survivors in making lifestyle changes. Results can be used to inform a subsequent randomised intervention study and integrate lifestyle coaching into care. TRIAL REGISTRATION: International Clinical Trial Registry Platform (ICTRP) number: NL8932 (ICTRP Search Portal [who. int]). Registered on 29 September 2020.
Keywords: dospělí; přežívající onkologičtí pacienti; Telemedicine; Female; dítě; Healthy Lifestyle; Adult; mladý dospělý; ženské pohlaví; Neoplasms; Life Style; životní styl; nádory; Adolescent; lidé; cvičení; telemedicína; Cancer Survivors; Male; zdravý životní styl; Young Adult; index tělesné hmotnosti; Child; mužské pohlaví; Exercise; Body Mass Index; mladiství; Humans